2022
DOI: 10.1001/jamanetworkopen.2022.42240
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Herpes Zoster Risk Among Recipients of COVID-19 Vaccine

Abstract: ImportanceHerpes zoster infection after COVID-19 vaccination has been reported in numerous case studies. It is not known whether these cases represent increased reporting or a true increase in risk.ObjectiveTo assess whether COVID-19 vaccination is associated with an increased risk of herpes zoster infection.Design, Setting, and ParticipantsThis cohort study used a self-controlled risk interval (SCRI) design to compare the risk of herpes zoster in a risk interval of 30 days after COVID-19 vaccination or up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…A cohort study published by Akpandak et al (2022) assessed whether vaccination against SARS-CoV-2 was associated with an increased risk of herpes zoster infection [30]. No increased risk was found [30]. This is an example of a signal derived from case reports that was not supported by properly conducted epidemiological studies, suggesting the initial reports were coincidental.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cohort study published by Akpandak et al (2022) assessed whether vaccination against SARS-CoV-2 was associated with an increased risk of herpes zoster infection [30]. No increased risk was found [30]. This is an example of a signal derived from case reports that was not supported by properly conducted epidemiological studies, suggesting the initial reports were coincidental.…”
Section: Discussionmentioning
confidence: 99%
“…This may include conducting vaccine studies, for example, via case-crossover designs which are used to study transient effects on the risk of acute events, and involves the patient acting as his or her own control [29]. A cohort study published by Akpandak et al (2022) assessed whether vaccination against SARS-CoV-2 was associated with an increased risk of herpes zoster infection [30]. No increased risk was found [30].…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all (c. 90%) of the reactivations were non-serious, with most manifestations being skin rashes showing dermatomal distributions which appeared within 10 days of the first vaccine dose. Other studies [ 59 ] have failed to identify an association between COVID-19 vaccination and herpes zoster. Akpandak et al [ 59 ] undertook a cohort study using a self-controlled risk interval (SCRI) design to compare the risk of herpes zoster in a risk interval of 30 days after COVID-19 vaccination, or up to the date of the second vaccine dose.…”
Section: Sars-cov-2 Vaccination and Human Herpesviruses Infectionsmentioning
confidence: 99%
“…Other studies [ 59 ] have failed to identify an association between COVID-19 vaccination and herpes zoster. Akpandak et al [ 59 ] undertook a cohort study using a self-controlled risk interval (SCRI) design to compare the risk of herpes zoster in a risk interval of 30 days after COVID-19 vaccination, or up to the date of the second vaccine dose. Among 2,039,854 subjects who received any dose of a COVID-19 vaccine during the study period (11 December 2020 to 30 June 2021), a subset of 1451 patients was identified who had herpes zoster in either the risk or control period.…”
Section: Sars-cov-2 Vaccination and Human Herpesviruses Infectionsmentioning
confidence: 99%
“…Since the Pfizer/BioNTech vaccine was the most common type received in the database, the subgroup may be divided into receiving one dose or two doses of the vaccination to clarify the effect of the COVID-19 vaccine. 2,3 Third, the zoster vaccine is recommended for people over the age of 50; therefore, after excluding patients who have received the zoster vaccine, the average age of the remaining cohort will be younger (<50 years old), which may cause selection bias. However, the authors still tried their best to overcome the bias by using subgroup analysis for different age intervals.…”
mentioning
confidence: 99%